RJM car park and service center a feasibility study - Amihan, Romel; Angeles, John Marnie; Ponce de Leon, Eva marie; Macalalag, Dulce Corazon; Tansi, Joeven
Executive Summary - A need for product or service is a product of time and seldom of ingenuity. No product will fit the market unless it fits the need of the customers. This project was developed to provide solution to the traffic problem felt and observed by the inhabitants of city, though this is a profit but to help attain the dream of Iloilo - to have a clean and green environment by the year 2000. We believe that cleaning the streets of Iloilo does not only mean cleaning them of dust and dirt but of littering vehicles that impedes the flow of traffic and business.